Desamparo psíquico na contemporaneidade - Oliveira, Adriana Aparecida Almeida de [UNESP]; Resstel, Cizina Célia Fernandes Pereira [UNESP]; Justo, José Sterza [UNESP] (My University, 2014)
This article has as a purpose to make a theoretical reflection on the experience of helplessness in the recent days. It starts from the Freud’s concept of helplessness, and compares it with analyses and reflections from contemporary authors on models of subjectivation which have risen at the present time. In the first experiences of life helplessness comes out as a result of an incompleteness of the organism, its need to perform exchanges with the world, and the extreme dependency on help from others. On the one hand, the contemporary culture highlights the individualism, which indicates good possibilities for granting desires. On the other hand, it makes bonds and relationships ephemeral and fragile. At the absence of a solid, safe and stable continent for affective and emotional experiences a feeling of helplessness appears. It activates primary defense mechanisms, contributing to the intensification of regressive forms of subjectivation and the decline of the symbolic sphere.

O presente artigo se propõe a fazer uma reflexão teórica da experiência de desamparo na atualidade, partindo da conceituação do desamparo por Freud e confrontando com análises e reflexões de autores contemporâneos sobre modelos de subjetivação que se despontam nos dias atuais. O desamparo aparece, já nas primeiras experiências da vida, como resultado da incompletude do organismo, de sua necessidade de realizar trocas com o mundo e da extrema dependência da ajuda de outros. A cultura contemporânea acentua o individualismo, por um lado, acenando com maiores possibilidades de realização de desejos, por outro, tornando os vínculos e relacionamentos efêmeros e tênues. Na ausência de um continente sólido, seguro e estável para as experiências emocionais e afetivas surgem sentimentos de desamparo que ativam mecanismos de defesas primitivos, contribuindo para a acentuação de formas de subjetivação regressivas e para o declínio do simbólico.
Psychic helplessness in contemporaneity
Keywords: Psychoanalysis; Helplessness; Contemporaneity; Psicanálise; Desamparo; Contemporaneidade